2015
DOI: 10.1038/ncomms7936
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity enhances ecosystem multifunctionality across trophic levels and habitats

Abstract: The importance of biodiversity for the integrated functioning of ecosystems remains unclear because most evidence comes from analyses of biodiversity's effect on individual functions. Here we show that the effects of biodiversity on ecosystem function become more important as more functions are considered. We present the first systematic investigation of biodiversity's effect on ecosystem multifunctionality across multiple taxa, trophic levels and habitats using a comprehensive database of 94 manipulations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
516
2
8

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 608 publications
(553 citation statements)
references
References 45 publications
27
516
2
8
Order By: Relevance
“…β-diversity | biodiversity | ecosystem functioning | FunDivEUROPE | spatial scale I t is widely established that high local-scale biodiversity increases levels of individual ecosystem functions in experimental ecosystems (1)(2)(3)(4), and that biodiversity is even more important for the simultaneous maintenance of multiple functions at high levels (i.e., ecosystem multifunctionality) (5)(6)(7)(8). Because the capacity of natural ecosystems to maintain multiple functions and services is crucial for human well-being (9), the positive Significance Numerous studies have demonstrated the importance of biodiversity in maintaining multiple ecosystem functions and services (multifunctionality) at local spatial scales, but it is unknown whether similar relationships are found at larger spatial scales in real-world landscapes.…”
mentioning
confidence: 99%
“…β-diversity | biodiversity | ecosystem functioning | FunDivEUROPE | spatial scale I t is widely established that high local-scale biodiversity increases levels of individual ecosystem functions in experimental ecosystems (1)(2)(3)(4), and that biodiversity is even more important for the simultaneous maintenance of multiple functions at high levels (i.e., ecosystem multifunctionality) (5)(6)(7)(8). Because the capacity of natural ecosystems to maintain multiple functions and services is crucial for human well-being (9), the positive Significance Numerous studies have demonstrated the importance of biodiversity in maintaining multiple ecosystem functions and services (multifunctionality) at local spatial scales, but it is unknown whether similar relationships are found at larger spatial scales in real-world landscapes.…”
mentioning
confidence: 99%
“…These values bracket all but the lowest of the four social cost estimates recommended for use in U.S. government regulatory analyses (35). Estimates of the coefficient of relative risk aversion in agriculture vary widely, and we explore the implications for optimal species composition of a correspondingly wide range of values, [0,2,4]. To put these parameter values in context, the certainty equivalent value of a gamble to win $100 or lose $50 with equal probability would be $25, $2.50, and $0.25, respectively, given the utility function identified above.…”
Section: Economic Datamentioning
confidence: 99%
“…Experimental evidence shows that, on average, as the level of diversity rises so too do measures of ecosystem functioning, such as primary production and carbon storage. The relationship applies not only to single ecosystem functions, but to many functions taken together--so-called "ecosystem multifunctionality" (3,4). Moreover, the temporal stability of ecosystem function increases with greater levels of diversity (5,6).…”
mentioning
confidence: 99%
“…In this context, the presented model can inform planners on the ecological functioning of coastal areas and provide baseline information for the development of ecosystem-based management strategies, required by the MSFD. For marine conservation planning, the presented MES model requires further methodological and dataset integrations related to field measurements on benthic communities distribution coupled with predictive model to assess benthic community distribution (Puls et al, 2012), assessment of ecological multi-functionality through geostatistical techniques (Lefcheck et al, 2015;Schröter and Remme, 2016), development of habitat fragmentation models to better understand ecological resilience (Cognetti and Maltagliati, 2010), identification of socio-economic proxy indicators that link ecological functioning and services to human well-being and 5) extension of sensitivity analysis implemented in the presented CI model, by defining the 407 408 409 410 411 412 413 414 415 416 417 418 419 420 421 422 423 424 425 426 427 428 429 430 431 432 433 434 435 436 437 438 439 440 441 442 443 444 445 446 447 448 449 450 451 452 453 454 455 456 457 458 459 460 sensitivity of a benthic habitat from anthropogenic pressures based on key stone species specific sensitivities and their ecological function (Depellegrin and Pereira 2016;Hooper et al, 2017). The presented MES model is a first step towards a wider MES analysis in the Adriatic Sea.…”
Section: Future Developmentsmentioning
confidence: 99%